Electronic Public Relation (E-PR): Strategi Mengelola Organisasi di Era Digital - Muhammad Anshar (Jurnal Komodifikasi, 2019)
The presence of the internet that supports public relations (PR) activities make a new concept namely Electronic Public Relations (E-PR). Some components related to the application of E-PR are: the use of electronic technology, especially the internet; building relationships as the core of public relations; serving the public inside (internal public) or outgoing (external public); and the type of organization itself can be a government agency, a private company (profit), or a social organization (non-profit). Defenition of Public Relations is communication management to build a good and positive relationship between an organization and its public. The Internet facilities that have been used in E-PR include: a web site; e-mail (electronic mail); mailing list; social media; chat application (direct communication); and applications of Management Information System (SIM).